Nonformal Education Strategy Enhancing Learning Motivation And Discipline To Prevent Dropout In Sijunjung - Dony Novaliendry; Yustitia Harti; Vitselly Marlinda Rizalfitri; Razifa Mutiara Hani; Arini Nisaul Khaira; Sapta Dewi Samudra; Sandra Agustin (Institut Teknologi dan Bisnis Asia Malang, 2026)
Purpose: This study addresses low learning motivation and school dropout risks among children in Sijunjung, West Sumatra, by implementing a non-formal education intervention. Method: A one-week community engagement program employed participatory methods, including interactive activities in literacy, numeracy, science, and sports, tailored to children's developmental levels; data were collected through observation and interviews. Practical Applications: The program offers a replicable, community-based model that integrates play-based learning with academic skill-building, providing practitioners and policymakers with strategies to enhance early childhood engagement in underserved areas. Conclusion: Significant improvements in children's learning eagerness, basic numeracy understanding, and communication confidence demonstrate that enjoyable, structured non-formal education can strengthen educational foundations and potentially mitigate future dropout rates.